Effect of Na excess on the dielectric and piezoelectric properties of (Na0.53K0.47)(Nb0.55Ta0.45)O3 ceramics. Issue 8 (3rd April 2014) - Kim, Jin Soo; Lim, Sang Yun; Ryu, Gyung Hyun; Hussain, Ali; Song, Tae Kwon; Park, Tae Gone; Park, Jongkyu; Kim, Won Jeong; Kim, Myong Ho
<x xml:space="preserve">Abstract</x> Na‐excess (Na0.53+xK0.47)(Nb0.55Ta0.45)O3 ceramics (x = 0.0, 0.005, 0.01, 0.015, 0.02, and 0.03) were prepared through the solid‐state reaction method. The effects of Na excess and Ta substitution on dielectric behaviors and piezoelectric properties were investigated. Crystallized single phases were confirmed using X‐ray diffraction. In particular, the orthorhombic–tetragonal polymorphic phase‐transition temperature (TO–T) was observed near room temperature, and the piezoelectric properties were enhanced, even for small Na excesses and Ta substitution. The optimized piezoelectric coefficient d33 and planar electromechanical coupling coefficient kp were estimated to be 320–340 pC/N and 0.36, respectively.